Faktor Yang Berhubungan Dengan Keluhan Low Back Pain Pada Perawat RSUD Dr. Lapalaloi Maros - Nur Mutihana; Ikhram Hardi; Fatmah Afrianty Gobel (Window of Public Health Journal, 2025)
Low back pain is a recurring ergonomic issue in occupational health and safety implementation, resulting in financial losses due to reduced worker capacity and productivity. If low back pain that occurs in nurses is not adequately handled, it will not only cause prolonged pain and discomfort, but can also lead to frustration and lifelong disability. This can negatively impact the quality of life for nurses themselves. If low back pain suffered by nurses during transfers also impacts the quality of hospital services in general. The purpose of this study was to identify the factors associated with workload, length of service, and work position that contribute to complaints of low back pain among nurses. This study employed a quantitative research method, utilizing an analytical survey approach, and employed a cross-sectional study design. The sampling technique used in this study was total sampling. The population in this study consisted of all nurses at Dr. Lapalaloi Regional Hospital, Maros Regency, totaling 39 nurses. Data were obtained using a questionnaire. The analytical methods employed were univariate and bivariate analyses, utilizing the chi-square test. The results of the study showed that there was no relationship between work period (p-value = 0.605> 0.05%) and low back pain complaints, there was a significant relationship between work position (p-value = 0.032<0.05%) and workload (p-value = 0.036<0.05%) with low back pain complaints in nurses at Dr. Lapalaloi Regional General Hospital, Maros Regency. The suggestion in this study is that workers should pay more attention to their health and working conditions to avoid health problems, including complaints of lower back pain.